Economic Impact of Ultra Micro Financing on Poverty Alleviation Among Woman in Rural Communities: Case Study Amartha - Agusria, Putri Nandi Pinta (Riviera Publishing, 2025)
Financial technology has revolutionized access to capital for marginalized communities, particularly women entrepreneurs in rural areas. This study investigates the impact of ultra-microfinancing on poverty alleviation among women in Indonesia through a case study of Amartha, a peer-to-peer (P2P) lending platform. The research explores the regulatory environment, economic impact on woman and technological accessibility affecting financial inclusion in underserved communities. Women in rural Indonesia often struggle with financial exclusion due to lack of credit history, collateral, and formal employment. Traditional banking institutions have largely ignored this demographic, leaving a gap that fintech platforms like Amartha aim to fill. Amartha provides microloans to women entrepreneurs, enabling them to start or expand businesses, thereby increasing household income and fostering local economic growth. Since its inception in 2010, Amartha has empowered over 1.5 million women, demonstrating the transformative potential of fintech in poverty reduction. This research is driven by key questions regarding business strategy and economic impact. The study employs a mixed-method approach, combining qualitative and quantitative data. Primary data includes surveys and interviews with Amartha’s management and mitra (partners), while secondary data is sourced from company reports, academic literature, and regulatory documents. The research also integrates economic models, financial inclusion frameworks, and risk management theories to assess Amartha’s effectiveness.